MONITORING THE SPECTRUM OF THE URINARY TRACT MICROBIOME AND INVESTIGATING DRUG-RESISTANT FORMS AFTER THE COVID-19 PANDEMIC - Olena V. Vlasova; Hanna L. Pustovoyt; Tatyana I. Yarmola; Nataliia V. Moisieieva; Iulia A. Kostrikova; Anatolii A. Miahkokhlib (Клінічна та профілактична медицина)
Introduction. Analysis of the experienced COVID-19 pandemic, during which the use of antimicrobial drugs significantly increased, contributed to the greater spread of antibiotic resistance in the world, and led to the appearance of more "aggressive" forms of pathogens. It is imperative to study the impact of the COVID-19 pandemic on the growth of antimicrobial resistance in patients with urinary tract infections in order to improve the effectiveness of treatment.